The relationship between strategic management planning and leadership skills - Nurul Wan Syafikah Yaakub; Brahim Chekima; Rudy Ansar; Suddin Lada (Penerbit UMS, 2022)
In this futuristic epoch, in which management transformation is taking place widely, leadership is emerging as one of the essential concepts in an organization trying to improve its performance effectively. Leadership is no longer a simple or easy concept, as most writers and researchers in this field mention. To explain how this leadership is practiced in detail, several models have been constructed by several researchers. Each of these models has qualities and can translate the elements of leadership in the organization well. These leadership models are built to move leaders and organizations toward integrated action in implementing leadership concepts. This study is a descriptive study using a systematic method of quantitative work. The primary source of this study is highlights of previous work obtained from the Scopus online database, Preferred Reporting Items for Systematic Reviews and Meta-Analysis (PRISMA). A total of 296 articles were shortlisted in this study. Precisely an organization will remain competitive if quality services are offered continuously.